2004
DOI: 10.1111/j.1365-2125.2004.02138.x
|View full text |Cite
|
Sign up to set email alerts
|

First‐trimester exposure to amoxycillin/clavulanic acid: a prospective, controlled study

Abstract: AimsThe number of published studies on the use of amoxycillin/clavulanic acid during pregnancy is small and so is the number of pregnancies investigated in those studies. In this study we wished to investigate prospectively the safety of intrauterine exposure to amoxycillin/clavulanic acid in a relatively large cohort of women. MethodsWomen treated ( n = 191) with amoxycillin/clavulanic acid during the first trimester of pregnancy were recruited from two teratogen information centres in Israel. Exposed women w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
4

Year Published

2005
2005
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 16 publications
1
11
0
4
Order By: Relevance
“…In a population-based case-control study [32] and a prospective controlled study [33], amoxicillin/clavulanic acid has been shown not to increase the teratogenic risk and is considered compatible with breastfeeding. These studies were, however, not specifically designed for patients with Crohn’s disease in which antibiotic treatment is generally given for an extended duration.…”
Section: Resultsmentioning
confidence: 99%
“…In a population-based case-control study [32] and a prospective controlled study [33], amoxicillin/clavulanic acid has been shown not to increase the teratogenic risk and is considered compatible with breastfeeding. These studies were, however, not specifically designed for patients with Crohn’s disease in which antibiotic treatment is generally given for an extended duration.…”
Section: Resultsmentioning
confidence: 99%
“…Tetracycline and sulfonamides are contraindicated in pregnancy (13) . Amoxicilin with or no clavulinic acid is compatible with breastfeeding and does not increase the risks for congenital anomalies (6) .…”
Section: D) Antibioticsmentioning
confidence: 98%
“…Ciprofloxacin and other quinolones have been used in pregnant women without evidence of congenital or musculoskeletal abnormalities in children and should be avoided its use in the first trimester (26) . However, more studies are needed to confirm (6) . Its use seems to be safe in breastfeeding (26) .…”
Section: D) Antibioticsmentioning
confidence: 99%
“…En general, dada además la escasa evidencia que existe de beneficio en EII, debe evitarse durante el embarazo 36 . Cuando se necesita un antibiótico, una buena elección sería la amoxicilina-ácido clavulánico, que corresponde a la categoría B de la FDA y cuyo uso no se ha asociado a teratogenicidad 82,83 . c) Glucocorticoides…”
Section: B) Antibióticosunclassified
“…Los datos disponibles sobre la utilización de quinolonas en la lactancia materna son limitados, pero es probable que sean compatibles 8,80 . La seguridad de la rifaximina en la lactancia materna es desconocida 6 y, por último, la amoxicilina-ácido clavulánico es compatible con la lactancia 82,83 . c) Glucocorticoides…”
Section: A) Salicilatosunclassified